Topological cavities in phononic plates for robust energy harvesting. (1st January 2022) - Wen, Zhihui; Jin, Yabin; Gao, Penglin; Zhuang, Xiaoying; Rabczuk, Timon; Djafari-Rouhani, Bahram
Graphical abstract: Piezoelectric energy harvesting has attracted tremendous interest for designing sustainable self-powered devices/systems targeted to special environment such as wireless or wearable applications. Hereby, the robust energy harvesting systems theoretically are proposed based on the topological cavities of the mechanical metamaterials, which are confined by the Kekulé distorted topological vortices. Highlights: The energy harvesting systems confined by the topological vortices are proposed. The topological harvesting peak is stable in frequency with high quality factor. Energy harvesting peak has is more feasible and controllable in functional design. The energy harvesting system is highly robust against defects and perturbation. Abstract: Piezoelectric energy harvesting has attracted tremendous interest for designing sustainable self-powered devices/systems targeted to special environment such as wireless or wearable applications. The traditional cavity (e.g., phononic cavity mode) excitation is highly applicable in terms of sufficient power generation, nevertheless, has to endure the drawback of extremely poor robustness intrinsic to the trivial cavity modes. We propose to use phononic thin plate systems for robust energy harvesting application relying on zero-dimensional cavities confined by the Kekulé distorted topological vortices. The harvesting power induced by topological cavities is about 30 times that of the bare plate. Further studies on the effects of deliberately introduced defects on the output power show that the proposed energy harvesting system is highly robust against symmetry-preserving defects, and is less influenced even for symmetry-breaking defects at moderate perturbation level. Beyond the reported energy harvesting application, we foresee that our work may open avenues for robust operations in the realm of wireless sensing and structural health monitoring.